RNA Sequencing Reveals the Expression Profiles of circRNAs and Indicates Hsa_circ_0070562 as a Pro-osteogenic Factor in Bone Marrow-Derived Mesenchymal Stem Cells of Patients With Ankylosing Spondylitis - Wang, Shan; Chen, Fenglei; Zeng, Chenying; Gu, Huimin; Wang, Ziming; Yu, Wenhui; Wu, Yanfeng; Shen, Huiyong (Frontiers in Genetics, 2022)
Recent studies have reported that circular RNAs (circRNAs) play a crucial regulatory role in a variety of human diseases. However, the roles of circRNAs in pathological osteogenesis in ankylosing spondylitis (AS) remain unclear. We conducted circRNA and miRNA expression profiling of osteogenically differentiated bone marrow-derived mesenchymal stem cells (BMSCs) of patients with AS compared with those of healthy donors (HDs) by RNA sequencing (RNA-seq). Results showed that a total of 31806 circRNAs were detected in the BMSC samples, of which 418 circRNAs were significantly differentially expressed (DE) with a fold change ≥ 2 and p value < 0.05. Among these, 204 circRNAs were upregulated, and 214 were downregulated. GO and KEGG analyses demonstrated that the DE circRNAs were mainly involved in the regulation of biological processes of the cell matrix adhesion and the TGF-beta signaling pathway, which are closely related to AS. circRNA-miRNA interaction networks related to the TGF-beta signaling pathway were established. The results of qRT-PCR showed that has_circ_0070562 was significantly up-regulated in AS-MSCs. In vitro experiments showed that silencing of has_circ_0070562 weakened osteogenesis of AS-BMSCs. In conclusion, we identified numerous circRNAs that were dysregulated in AS-BMSCs compared with HD-BMSCs. Bioinformatic analyses suggested that these dysregulated circRNAs might play important functional roles in AS-BMSCs osteogenesis. Circ_0070562 functioned as a pro-ostegenic factor and might serve as a potential biomarker and a therapeutic target for AS.